Impact Analysis of Human Activities on Mangrove Conservation in Coastal Sulawesi - Evelin Anggelina Tanur; Hamzah Al Imran; Rusdi Angrianto; Nunang Lamaek May; Arniana Anwar (West Science Nature and Technology, 2024)
Mangrove ecosystems are invaluable coastal habitats that provide essential ecological services and support diverse flora and fauna. However, human activities have increasingly threatened the sustainability of these ecosystems, particularly in regions like Coastal Sulawesi, Indonesia. This qualitative analysis investigates the impact of human activities on mangrove conservation in Coastal Sulawesi, employing semi-structured interviews, participant observation, and document analysis. The study reveals that drivers such as aquaculture expansion, unsustainable logging, pollution, and coastal development are contributing to mangrove degradation. Stakeholder perspectives vary, with local communities emphasizing the importance of mangroves for livelihoods and culture, while government officials stress the need for balancing conservation with economic development. Existing conservation efforts include protected area designation, community-based management projects, and awareness-raising campaigns. Collaborative action involving government, NGOs, academia, and local communities is essential to promote sustainable mangrove conservation in Coastal Sulawesi.